Prospective associations of interleukin‐6 and APOE allele with cognitive decline in biracial community‐dwelling older adults: The Chicago Health and Aging Project (CHAP) - Ted K. S. Ng; Todd Beck; Pankaja Desai; Klodian Dhana; Robert S. Wilson; Denis A. Evans; Kumar B. Rajan (Alzheimer’s & Dementia: Diagnosis, Assessment & Disease Monitoring)
Abstract INTRODUCTION It is unclear whether inflammation, that is, high interleukin‐6 (IL‐6) levels, and genetic risk, that is, apolipoprotein E (APOE) ε4 allele, have a compounding effect on cognitive decline (CD). METHODS We analyzed a subset of participants from the longitudinal cohort study, Chicago Health and Aging Project, comprising 1120 biracial community‐dwelling older adults (60% Black and 62% women), and mean follow‐up = 6.4 years. We ran adjusted mixed‐effects models on2 longitudinal CD. RESULTS In APOE ε4 carriers, higher serum IL‐6 was not associated with the rate of CD (β = –0.0091 [standard deviation (SD) = 0.0165, p = 0.5800]). Conversely, in non‐ε4 carriers, compared to the lower tertile, those with the upper tertile of serum IL‐6 levels experienced significantly accelerated CD (β = –0.0257 [SD = 0.0084, p = 0.0023]). DISCUSSION Even without the largest genetic risk factor for late‐onset Alzheimer's disease/Alzheimer's disease and related dementias (AD/ADRD), elevated serum IL‐6 still accelerate the rate of CD in non‐APOE ε4 carriers. Hence, interventions ameliorating inflammation may prevent AD/ADRD. Highlights Interleukin‐6 (IL‐6) and the apolipoprotein E (APOE) ε4 allele have been separately associated with an increased risk for cognitive decline, but their interaction remains unclear. In ε4 carriers, IL‐6 was not associated with cognitive decline. However, even without the biggest genetic risk factor for Alzheimer's disease (AD), that is, APOE ε4, elevated serum IL‐6 still could confer accelerated rate of cognitive decline, with a detrimental effect half of that imposed by APOE ε4 alone. We found no racial differences in these associations. These findings contribute complementary evidence on non–APOE ε4‐dependent and non‐AD biological pathways through which cognitive decline can still be accelerated in non‐APOE ε4 carriers and highlight a specific subgroup of older adults who are at a higher risk of AD and thus may benefit from anti‐inflammatory interventions.